Naturaleza caída y sujeto melancólico - Espinosa, Luciana (ARFIL y UNL, 2018)
In this paper we argue that Walter Benjamin’s approach to the problem of melancholy in The origin of German tragic drama (1928) brings an access to the deep structure of the material world through the establishment of a unique relationship between the melancholic human being and fallen nature. Therefore, if, as Benjamin says, every feeling is the result of an object or some material conformation that operates as its cause, melancholy, for its part, is that feeling emerged from the deep regret of nature revealed by the means of a language able to contemplate the sadness which constitutes it and the pain that generates the impossibility of redemption.